2022
DOI: 10.1021/acs.nanolett.2c01945
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Index SiO2 Antireflection Coatings Produced via Magnetron Sputtering

Abstract: Antireflection (AR) coatings with graded refractive index profiles approaching air offer unparalleled AR performance but lack a scalable fabrication process that would enable them to be used more widely in applications such as architecture and solar energy conversion. This work introduces a sputtering-based sacrificial porogen process to fabricate multilayer nanoporous SiO 2 coatings with tunable refractive index down to n eff = 1.11. Using this approach, we demonstrate a step-graded bilayer AR coating with ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Prior studies have shown that incorporating a refractive index gradient across the thickness of a film is an efficient method to produce a broadband ARC. ,, To produce such a structure, we infiltrate subsaturating amounts of PMMA into the disordered packings of hollow NPs. To control the extent of UCaRI, we define the volume fraction of PMMA in each film as ϕ PMMA = h PMMA h NP , where h PMMA and h NP are the thicknesses of the PMMA layer and hollow silica NP layer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have shown that incorporating a refractive index gradient across the thickness of a film is an efficient method to produce a broadband ARC. ,, To produce such a structure, we infiltrate subsaturating amounts of PMMA into the disordered packings of hollow NPs. To control the extent of UCaRI, we define the volume fraction of PMMA in each film as ϕ PMMA = h PMMA h NP , where h PMMA and h NP are the thicknesses of the PMMA layer and hollow silica NP layer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with atomic layer deposition methods, magnetron sputtering has a faster preparation speed and larger preparation area, which is necessary for commercial applications. In addition, this process does not require a high-temperature annealing step in comparison to alternative method of producing films with low refractive index using the sputtering–annealing–etching process . This significantly reduces the cost of production and allows the process to rapidly produce ultralow refractive coatings on optical glasses with lower melting points .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this process does not require a high-temperature annealing step in comparison to alternative method of producing films with low refractive index using the sputtering−annealing−etching process. 37 This significantly reduces the cost of production and allows the process to rapidly produce ultralow refractive coatings on optical glasses with lower melting points. 38 However, similar to other methods for preparing low refractive index coatings using increased porosity, the NS coatings prepared by this process do not perform well enough in terms of mechanical properties, and the test results on the hardness of the NS films are shown in Figure S6, Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In order to overcome this problem, one can consider another light absorbing scheme, i.e., the design of graded-refractive-index (GRI) thin dielectric layers on the metallic mirror. [12,13] However, it is a great challenge to design such SMAs within a short time. Conventionally, it relies on broadband impedance matching in the entire solar spectrum, and this demands numerous experiments, optical simulations, and some classical algorithms to optimize layer thicknesses.…”
Section: Introductionmentioning
confidence: 99%